Experimental Studies of Interaction Forces Affect the Position of Vertical Plates on Oscillating Heave Plates with Cylindrical Bodies in Regular Waves - Eko Sasmito Hadi; Muhammad Iqbal; Ari Wibawa; Ojo Kurdi; Karnoto Karnoto (International Journal of Renewable Energy Development, 2020)
This paper discusses an experimental study of a wave energy converter (WEC) without using reaction from the seabed. The WEC uses buoys and heave plates, which can react to their self-reacting. The interaction force between heave plates and buoys can absorb energy from ocean waves better. The heave plate model affects the output of energy produced. It is presented in this study with variations in the position of upright plates. The research aims to measure the influence of the place of the addition of vertical plates into heave plates on the WEC on the hydrodynamic performance (coefficient of mass increase, drag coefficient, and KC value) and the interaction of the force it produces with the buoy on regular waves. The conclusion is the vertical plate position makes the coefficient of mass added Ca increase with an increasing amount of KC, and an almost linear relationship was observed between them. As the frequency increases, the value of C increases slightly, but it is not clear. Thus, the oscillating frequency has little effect on the mass coefficient of added heave plates with vertical plates. Thus, the change in the vertical plate position has only a powerful effect on KC < 0.75. ©2020. CBIORE-IJRED. All rights reserved